Gender Differences in Prefrontal Cortex Response to Negative Emotional Stimuli in Drivers - Ferran Balada; Anton Aluja; Óscar García; Neus Aymamí; Luis F. García (Brain Sciences, 2024)
Background: Road safety improvement is a governmental priority due to driver-caused accidents. Driving style variation affects safety, with emotional regulation being pivotal. However, functional near-infrared spectroscopy (fNIRS) studies show inconsistent prefrontal cortex activity during emotion processing. This study examines prefrontal cortex response to negative emotional stimuli, particularly traffic accident images, across drivers diverse in age and gender. Method: The study involved 118 healthy males (44.38 ± 12.98 years) and 84 females (38.89 ± 10.60 years). The Multidimensional Driving Style Inventory (MDSI) was used to assess driving behavior alongside fNIRS recordings. Participants viewed traffic accident and neutral images while prefrontal oxygenation was monitored. Results: Women rated traffic accidents (t-test = 2.43; p < 0.016) and neutral images (t-test = 2.19; p < 0.030) lower in valence than men. Arousal differences were significant for traffic accident images (t-test = −3.06; p < 0.002). correlational analysis found an inverse relationship between Dissociative scale scores and oxygenation (all p-values ≤ 0.013). Greater prefrontal oxygenation occurred with neutral images compared to traffic accidents. Left hemisphere differences (t-test = 3.23; p < 0.001) exceeded right hemisphere differences (t-test = 2.46; p < 0.015). Subgroup analysis showed male participants to be driving these disparities. Among adaptive drivers, significant oxygenation differences between neutral and accident images were evident in both hemispheres (left: t-test = 2.72, p < 0.009; right: t-test = 2.22, p < 0.030). Conclusions: Male drivers with maladaptive driving styles, particularly dissociative ones, exhibit reduced prefrontal oxygenation when exposed to neutral and traffic accident images. This response was absent in female drivers, with no notable age-related differences.